Analisis Id, Ego, dan Supergo pada Tokoh Lolita dalam Novel Secret Obsession Karya Anggarani - Adi Krisnanto; Bayu Septiana Sadewa; Eva Dwi Kurniawan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Id, ego and super-ego are separate psychic structures in humans but interact with each other. This concept was formulated by Sigmund Freud. This journal discusses the id, ego and super-ego in the literary work of the novel entitled Secret Obsession by Angkai. The problem of this research is how the id, ego and super-ego influence the behavior of the main character in the novel entitled Secret Obsession by Budgeti. The method used in this research uses a literary psychology approach with Sigmud Freud's psychoanalysis theory regarding the id, ego and super-ego of the character Lolita in the novel Secret Obsession by Budgeti. The results of this research can be concluded that Lolita shows more mature ego development, is able to control the id's feelings of pleasure and interact more realistically. Additionally, Lolita's superego side shows moral evolution, such as guilt, regret, and the drive to become a better person. The factors that influence the development of Lolita's character consist of the people around her, the environment, and hurt feelings. Analysis is carried out from the beginning, middle, to the end of the story, showing significant character evolution.